Copyright protection of foreign works in Malaysia / Zuraida Mohd Zabidi - Mohd Zabidi, Zuraida (Faculty of Law, 1985)
Malaysia did not have a comprehensive legislation on copyright until 1969. The legislation relating to the copyright in the Malay states comprised the Federated Malay States Copyright Enactment 1935. The United Kingdom Copyright Act 1911 applied as extended to the Straits Settlements and the United Kingdom Copyright Act 1956 as extended, to the states of Sabah and Sarawak. While in the former Unfederated Malay States, there was no copyright law in operation. The committee responsible for preparing the Copyright Bill 1969 (as it was then called) based its work mainly on several laws, taking as its model the Nigerian Copyright Bill which was specially drawn up for a developing country. The committee also made use of materials, study papers and working papers that were presented at the Asian Seminar On Copyright held in New Delhi in January, 1967 and the protocol for developing countries introduced at the Revision Conference of the Berne Convention held in Stockholm in June 19678 . The Malaysian law in respect of copyright underwent a revision and consolidation which provide a uniform copyright law for the whole of Malaysia. The Copyright Bill 1969 as it was then called, was also intended to be an improvement on the proposed Copyright Bill of 1967 which was published in the government gazette of June 1967. Copyright now subsists by virtue of this Act only.